Borrelia miyamotoi Serology in a Clinical Population With Persistent Symptoms and Suspected Tick-Borne Illness - Delaney, Shannon L.; Murray, Lilly A.; Aasen, Claire E.; Bennett, Clair E.; Brown, Ellen; Fallon, Brian A. (Frontiers in Medicine, 2020)
82 patients seeking consultation for long-term sequalae after suspected tick-borne illness were consecutively tested for Borrelia miyamotoi antibodies using a recombinant glycerophosphodiester phosphodiesterase (GlpQ) enzyme immunoassay. 21 of the 82 patients (26%) tested positive on the GlpQ IgG ELISA. Nearly all of the patients (98%) had no prior B. miyamotoi testing, indicating that clinicians rarely test for this emerging tick-borne pathogen. Compared to patients who solely tested positive for Lyme disease antibodies, patients with B. miyamotoi antibodies presented with significantly more sleepiness and pain. A prospective study is needed to ascertain the relationship between the presence of B. miyamotoi antibodies and persistent symptoms.